Encumbrance of Mortgage Rights on Uncertified Land - Gautam Kumar Jha; Ni Komang Arini Styawati; I Nyoman Sumardika (Fakultas Hukum, Universitas Warmadewa, 2022)
In the General Explanation of Mortgage Law (UUHT) it is stated that there are two absolute elements of land rights that can be used as mortgage objects, one of which is that the right in accordance with applicable provisions shall be registered at the Land Office. Thus, every Mortgage Object shall be registered and have a land title certificate. Nevertheless, on land having not been certified, Mortgage Rights may also be charged as long as the grant is carried out at the same time as the application for registration of the land rights in question. The problem is how to carry out the registration of mortgage rights on uncertified land and what are the legal consequences of granting mortgage rights to uncertified land rights? This study uses a juridical-empirical research method. There are two types of data used, such as primary and secondary data. The encumbrance of Mortgage Rights on land having not been certified has never been carried out by banks by making a Deed of Encumbrance of Mortgage Rights (APHT) directly. Banks are only limited to making a Power of Attorney to Charge Mortgage (SKMHT) only. The consideration for not making APHT for land that has not been registered is because the ownership of the titles to the land is not yet clear. In practice, Notaries/Land Deed Officials always make SKMHT in accordance with Article 15 (4) UUHT to bind collateral for land that has not been certified. This is an obstacle because the certification process takes more than 3 months, even a year. In dealing with problems in the form of unpaid loans with uncertified land collateral, while the debtor has died and left an heir, then there are several ways of settling the bank, such as: if the credit is due, then the payment is taken over by credit insurance. If the credit has matured and the credit insurance has expired, it will be billed until it is paid off to the heirs in a family manner by offering interest relief on the loan, asking the heirs concerned to make an underhand sale of the object of the guarantee.